2003
DOI: 10.1007/s00122-003-1409-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs associated with Fusarium head blight resistance in Zhedar 2 barley

Abstract: Fusarium head blight (FHB) in barley and wheat, caused by Fusarium graminearum, is a continual problem worldwide. Primarily, FHB reduces yield and quality, and results in the production of the toxin deoxynivalenol (DON), which can affect food safety. Identification of QTLs for FHB severity, DON level and related traits heading-date (HD) and plant-height (HT) with consistent effects across a set of environments, would provide the basis for marker-assisted selection (MAS) and potentially increase the efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
68
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 33 publications
11
68
0
Order By: Relevance
“…2). Ma et al (2000), Mesfin et al (2003) and Dahleen et al (2003) reported the presence of QTLs for FHB on chromosome 6H. Some of the reported QTLs may correspond to the QTL detected in the present study.…”
Section: Qtl Analysis For Fhb Resistancesupporting
confidence: 77%
See 4 more Smart Citations
“…2). Ma et al (2000), Mesfin et al (2003) and Dahleen et al (2003) reported the presence of QTLs for FHB on chromosome 6H. Some of the reported QTLs may correspond to the QTL detected in the present study.…”
Section: Qtl Analysis For Fhb Resistancesupporting
confidence: 77%
“…2). Mesfin et al (2003) and Dahleen et al (2003) also reported the presence of QTLs for FHB severity in the vicinity of the vrs1 locus on chromosome 2H in two-rowed × six-rowed populations. Thus, the vrs1 locus might exert a pleiotropic effect conferring FHB resistance, but may not be the major factor for FHB resistance.…”
Section: Qtl Analysis For Fhb Resistancementioning
confidence: 90%
See 3 more Smart Citations